Pilkada Calon Tunggal dalam Perspektif Siyasah Syari’yyah - Asiyah, Asiyah; Riza, Fikri; Kurniadi, Rahmad; Riyadi, Ahmad; Nur, Muhammad; Andriansyah, Muhammad; Joanda, Ivan Rahmat (Tasyri' : Journal of Islamic Law, 2025)
The phenomenon of regional head elections (Pilkada) with a single candidate creates tension between the principles of democracy and the concept of siyasah syar'iyyah in Islamic politics. This study aims to analyze the implications of a single candidate in the Regional Elections from the perspective of siyasah syar'iyyah, especially in relation to the principles of justice, deliberation (shura), and the benefit of the people. This study uses a qualitative method with a literature approach to examine the views of scholars and regulations that govern the single-candidate Regional Elections. The results of the study show that this phenomenon occurs due to the dominance of political power, high political costs, and strict candidacy requirements, which lead to limited political competition. In Islam, leaders must be chosen through a fair and transparent process, but in an emergency, a pragmatic approach allows for a single candidate for the sake of government stability. Instead, the idealistic approach emphasizes the importance of healthy deliberation and competition. Therefore, siyasah syar'iyyah offers solutions in the form of increasing political participation, reducing administrative obstacles, and guaranteeing transparency in the election process. In conclusion, single-candidate regional elections can be accepted under certain circumstances, but must still pay attention to the principles of democracy and justice so as not to conflict with the values of siyasah syar'iyyah.